An Efficient Method for Microphysical Property Retrievals in Vertically Inhomogeneous Marine Water Clouds Using MODIS‐CloudSat Measurements. Issue 4 (23rd February 2019) - Saito, Masanori; Yang, Ping; Hu, Yongxiang; Liu, Xu; Loeb, Norman; Smith, William L.; Minnis, Patrick
Abstract: An efficient method is developed to infer cloud optical thickness (COT) and cloud droplet effective radius (CDER) of marine water clouds from Moderate Resolution Imaging Spectroradiometer (MODIS) and CloudSat measurements, incorporating droplet size vertical inhomogeneity. Empirical orthogonal function (EOF) analysis is employed to reduce the degrees of freedom of the droplet size profile. The first two EOFs can explain 94% of the variability in the droplet size profile. Compared to the existing bispectral CDER retrieval from MODIS assuming plane parallel vertically homogeneous clouds, the new retrieval produces smaller CDER values in clouds in which the adiabatic growth process is dominant and larger CDER values in clouds in which the collision‐coalescence process is dominant. To evaluate the performance of the retrieval algorithm, we compare retrieved COT and CDER in this study with their MODIS and CloudSat counterparts on a pixel‐by‐pixel basis. CDER retrieval based on the vertically homogeneous assumption may be underestimated by 30% due to droplet size vertical inhomogeneity when COT is large and the collision‐coalescence process is dominant in the cloud. Retrieved CDER in conjunction with the two scores for EOFs can reconstruct the vertical profile of CDER, which is useful for cloud microphysical process studies. Furthermore, potential expansion of this algorithm to MODIS pixels without CloudSat collocations is discussed. Key Points: An efficient method for vertically inhomogeneous water cloud property retrievals is developed using empirical orthogonal functions Vertically homogeneous assumption may cause underestimated cloud droplet effective radius retrievals by maximum 30% The method reconstructs vertical profiles of cloud droplet effective radius, which is useful to cloud microphysical process studies